The RNA polymerase subunits E/F from the Antarctic archaeon Methanococcoides burtonii bind to specific species of mRNA - DE FRANCISCI D; KORNFELD G; SIDDIQUI KS; WILLIAMS TJ; ERTAN H; PILAK O; LAURO FM; HARROP SJ; CURMI PM; CAVICCHIOLI R.; CAMPANARO, STEFANO; TREU, LAURA (John Wiley & Sons, Inc., 2011)
RNA polymerase in Archaea is composed of 11 or 12 subunits - 9 or 10 that form the core, and a heterodimer formed from subunits E and F that associates with the core and can interact with general transcription factors and facilitate transcription. While the ability of the heterodimer to bind RNA has been demonstrated, it has not been determined whether it can recognize specific RNA targets. In this study we used a recombinant archaeal MbRpoE/F to capture cellular mRNA in vitro and a microarray to determine which transcripts it specifically binds. Only transcripts for 117 genes (4% of the total) representing 48 regions of the genome were bound by MbRpoE/F. The transcripts represented important genes in a number of functional classes: methanogenesis, cofactor biosynthesis, nucleotide metabolism, transcription, translation, import/export. The arrangement and characteristics (e.g. codon and amino acid usage) of genes relative to the putative origin of replication indicate that MbRpoE/F preferentially binds to mRNA of genes whose expression may be important for cellular fitness. We also compared the biophysical properties of RpoE/F from M. burtonii and Methanocaldococcus jannaschii, demonstrating a 50°C difference in their apparent melting temperatures. By using MbRpoE/F to capture and characterize cellular RNA we have identified a previously unknown functional property of the MbRpoE/F heterodimer.